2001
DOI: 10.1023/a:1011662411913
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The P300 complex was derived from the electroencephalogram (EEG) as subjects mentally counted infrequent large checkerboard visual stimuli, presented randomly among frequent small checkerboard stimuli. Use of low contrast (10%) stimuli and four midline scalp electrodes, facilitated separation of cognitive and sensory components and enabled the P300 complex to be resolved into three distinct components--N200, P3a, and P3b. In 20 healthy adult subjects normative data were established and the P3a and P3b componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Ciećko-Michalska [ 31 ] suggested that ERPs are a more sensitive method than psychometric tests in detecting early changes in the brain function of patients with cirrhosis. In partial agreement, Jones et al [ 32 ] had also found in the visual ERP study that the prolongation of P300 latency in cirrhotic patients without overt hepatic encephalopathy (HE) may occur in the absence of abnormalities of a standard psychometric test.…”
Section: Discussionmentioning
confidence: 71%
“…Ciećko-Michalska [ 31 ] suggested that ERPs are a more sensitive method than psychometric tests in detecting early changes in the brain function of patients with cirrhosis. In partial agreement, Jones et al [ 32 ] had also found in the visual ERP study that the prolongation of P300 latency in cirrhotic patients without overt hepatic encephalopathy (HE) may occur in the absence of abnormalities of a standard psychometric test.…”
Section: Discussionmentioning
confidence: 71%
“…This forms preliminary evidence that the system's performance remains robust although event-related potentials may change over time [2527]. More research, however, is needed to verify the stability of the system's performance over long time periods.…”
Section: Conclusion and Discussionmentioning
confidence: 90%